2022
DOI: 10.1186/s13578-022-00776-9
|View full text |Cite
|
Sign up to set email alerts
|

UBIAD1 alleviates ferroptotic neuronal death by enhancing antioxidative capacity by cooperatively restoring impaired mitochondria and Golgi apparatus upon cerebral ischemic/reperfusion insult

Abstract: Background Neuronal death due to over-oxidative stress responses defines the pathology of cerebral ischemic/reperfusion (I/R) insult. Ferroptosis is a form of oxidative cell death that is induced by disruption of the balance between antioxidants and pro-oxidants in cells. However, the potential mechanisms responsible for cerebral I/R-induced ferroptotic neuronal death have not been conclusively determined. UBIAD1, is a newly identified antioxidant enzyme that catalyzes coenzyme Q10 (CoQ10) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…In nonmitochondrial systems, CoQ10 is involved in regulating lipid peroxidation, paralleling the GPX4 pathway in ferroptosis [ 98 ]. Huang et al [ 16 ] demonstrated that UBIAD1 was upregulated during cerebral I/R, which suppressed lipid peroxidation and ferroptosis and exerted neuroprotective effects. UBIAD1 alleviated cerebral I/R-mediated ferroptotic neuronal death by enhancing antioxidant capacities by ameliorating mitochondria and Golgi apparatus dysfunction, suggesting that restoring impaired mitochondria and the Golgi apparatus is beneficial in ameliorating cerebral I/R injury.…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…In nonmitochondrial systems, CoQ10 is involved in regulating lipid peroxidation, paralleling the GPX4 pathway in ferroptosis [ 98 ]. Huang et al [ 16 ] demonstrated that UBIAD1 was upregulated during cerebral I/R, which suppressed lipid peroxidation and ferroptosis and exerted neuroprotective effects. UBIAD1 alleviated cerebral I/R-mediated ferroptotic neuronal death by enhancing antioxidant capacities by ameliorating mitochondria and Golgi apparatus dysfunction, suggesting that restoring impaired mitochondria and the Golgi apparatus is beneficial in ameliorating cerebral I/R injury.…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…NO maintains endothelial function by promoting vasodilation and preventing vascular smooth muscle cell proliferation, platelet aggregation, and leukocyte adhesion [ 50 ]. The biosynthesis process of NO has also been found to associate with brain tissue damage and neuronal ferroptosis in the pathology of cerebral ischemic/reperfusion [ 51 ]. The KEGG results showed that the DETmRNAs were mainly enriched in the Toll-like receptor signaling pathway and the NF kappa B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, enrichment of Alloprevotella may be associated with an increase in serum trimethylamine N-oxide ( Cheng et al, 2017 ), and the latter is a potential causative factor of first and recurrent stroke ( Nam, 2019 ). Additionally, the abundance of fecal Alloprevotella was negatively correlated with serum total antioxidant activity ( Wang et al, 2021 ), and enhancing antioxidative capacity was found to be beneficial for alleviating cerebral ischemia/reperfusion insult ( Huang et al, 2022 ). All these data indicate that ANP administration can protect against stroke by decreasing the abundance of Prevotellaceae and Alloprevotella in the gut.…”
Section: Discussionmentioning
confidence: 99%